The Rice Proteogenomics Database OryzaPG-DB: Development, Expansion, and New Features - Helmy, Mohamed; Sugiyama, Naoyuki; Tomita, Masaru; Ishihama, Yasushi (Frontiers in Plant Science, 2012)
Proteogenomics is the utilization of large-scale proteome data in genome annotation refinement. Our recently developed rice proteogenomics database (OryzaPG-DB) is the first sustainable resource for rice shotgun-based proteogenomics, providing information on peptides identified in rice protein digested peptides measured by means of liquid chromatography-tandem mass spectrometry (LC-MS/MS), and mapping of the peptides to their genomic origins and the genomic novelty of each peptide. The sequences of the peptides, proteins, cDNAs and genes, and the gene annotations are available for download in FASTA and GFF3 formats, respectively. Further, an annotated visualization of the gene models, corresponding peptides and genomic novelty is available for each gene, and MS/MS spectra are available for each peptide. In this article, we discuss the utilization of OryzaPG-DB and report on its development, recent content expansions and newly added features in the current version (OryzaPG-DB v1.1).